Pembinaan dan penggunaan ujian diagnostik kearah mengenal pasti salah konsep pelajar dalam Kursus Fizik Kuantum - Abdul Halim,; T.Subahan bin Meerah,; Lilia Halim, (Universiti Kebangsaan Malaysia, 2009)
A study on students’ misconceptions on quantum physics is rarely being done, because the target audience is quite small. It is important to understand quantum physics concepts correctly especially for science students. This study was under taken to help students identify their misconceptions at the early stage. The aim of this study is to develop a diagnostic test which can access the students’ misconceptions, and use the findings for the benefits of quantum physics courses. A multiple-choice Quantum Physics Diagnostic Test (QPDT), that involves concepts of light, atomic model, particle-wave dualism, wave function, and potential energy, was administered to 200 university students. The results shows that many students use the classical concepts to describe the quantum phenomenon. For example students describe light only as a wave, an electron only as a particle, and that the atomic structure is parallel to the solar system. To overcome these problems, it is suggested that lecturers spend more time in explaining the basic definitions and using analogies in quantum physics teaching.